Taxonomic Analysis of Internet and ICT Usage in A Static and Dynamic Perspective in Selected European Countries and US States with Special Focus on The Time of The Covid-19 Pandemic - Anna JANIGA-ĆMIEL (Communications of International Proceedings, 2021)
The study examines the use of the internet and information and communication technologies by the citizens of the selected country, with special emphasis placed on the Covid-19 pandemic period. In the study, a taxonomic method (Chomątowski, Sokołowski, 1978), (Młodak, 2006) was employed to analyse the level of variation of objects described by selected statistical characteristics and identify clusters of objects sharing a similar level of development of the phenomenon under consideration. (Taxonomic method with modifications proposed by A. Młodak (Młodak, 2006)).The study covered the years 2010-2020, including the time of the Covid-19 pandemic. The analysis included in two stages, i.e. it covered two directions of the structure analysis: the static variant and the dynamic variant. First, Poland was analysed and the groups of voivodeships featuring a homogeneous level of development were identified. In the next step, the analysis was performed for the European countries to see how Poland compares to them. The last stage involved analysing the US states in regard to the phenomenon under study. The study is based on the data sourced from Poland Statistics, US Statistics and Eurostat websites.
Keywords: Econometric Methods; Information Society; Taxonomic Analysis